Het verhaal van Vlaanderen - Huybrechts, Yves; Schmitz, Sabine (BMGN - Low Countries Historical Review)
In deze bijdrage analyseren we Het verhaal van Vlaanderen vanuit het perspectief van een buitenstaander. Ten eerste bevragen wij het mediaformat van de televisieserie en ten tweede het beeld van de geschiedenis dat daarin wordt gehanteerd. Kan deze serie als een documentaire worden gecategoriseerd, of gaat het hier toch eerder om entertainment, of hebben we met een mengvorm te maken? En welk geschiedenisverhaal hanteert de serie? Dit beeld van de geschiedenis is niet duidelijk omdat de geografische focus van de reeks op het huidige Vlaanderen ligt. Wij betogen dat zowel het wisselende mediaformat alsook de variërende inhoud een rol speelt in de controverse die rond Het verhaal van Vlaanderen is ontstaan.

Züge und Räume‘, Annelies Verbeke: Verlorener Gesang. Mantel der Liebe. Erzählungen, 2023 - Schmitz, Sabine; Artois, Laurette (Alles außer flach. Essays über aktuelle Literatur aus den Niederlanden und Flandern)

Alles außer flach. Essays über aktuelle Literatur aus den Niederlanden und Flandern - Schmitz, Sabine; Weyrich, Marie ('Und man wird ja wohl noch träumen dürfen, oder?“, Joris Mertens: Das große Los, 2023)

Authenticité et patrimoine culturel. Genèse et adoption du critère d’autehnticité par la Convention du Patrimoine Mondial - Seng, Eva- Maria (Nouvelles lectures patrimoniales. Les Pays de la Loire au mirroir de l’Europe)

European Heritage Label. Selection. Report of the European Panel to the European Commission. 2021

Hankel transform, K-Bessel functions and zeta distributions in the Dunkl setting - Brennecken, Dominik (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

Modos de no ficción en RW. Rodolfo Walsh en historietas (2016) de Gonzalo Penas y CJ Camba - Schmitz, Sabine (Aux commencements des écritures du réel - Rodolfo Walsh (Argentine, 1927-1977))

Technische und ökonomische Implikationen des Einsatzes kunststoffbasierter additiver Fertigungsverfahren in der Produktion - Schulz, Pascal (Produktion, Logistik und Controlling im Zeitalter der Digitalisierung)

Entwicklung eins Tourenplanungsmodells zur Unterstützung der Wahl zwischen elektrisch und mit Diesel betriebenen LKW - Betz, Stefan (Produktion, Logistik und Controlling im Zeitalter der Digitalisierung)

Zielorientierte Steuerung durch ganzheitliches Unternehmenscontrolling in Krisensituationen - am Beispiel von Covid 19 - Christian, Koch (Produktion, Logistik und Controlling im Zeitalter der Digitalisierung)

Bestimmung des zieloptimalen Automatisierungsgrads ausgewählter Montagevorgänge - Plückebaum, Daniel (Produktion, Logistik und Controlling im Zeitalter der Digitalisierung)

Against all expectations? What are the differences between resilient and non-resilient schools in the CIL domain. - Lörz, Markus; Drossel, Kerstin; Eickelmann, Birgit; Fröhlich, Nadine (Social Sciences & Humanities Open,)

Industrial Internet of Things - Enabler der digitalen Transformation zur Smart Factory - Puls, Christoph (Produktion, Logistik und Controlling im Zeitalter der Digitalisierung)

Wandel im Controlling - Digitalisierung und ihre Auswirkungen auf den Personalbedarf - Koch, Christian (Produktion, Logistik und Controlling im Zeitalter der Digitalisierung)

Digitale Instrumente des Cost Engineering - Faupel, Christian (Produktion, Logistik und Controlling im Zeitalter der Digitalisierung)

Produktion, Logistik und Controlling im Zeitalter der Digitalisierung

Using academic mathematical knowledge when working on interface tasks–analyses of pre-service teachers’ arguments about rotationally symmetric figures - Hoffmann, Max; Biehler, Rolf (ZDM – Mathematics Education)
Abstract Special tasks for pre-service teachers (PSTs) in university mathematics courses (“interface tasks”) are a common innovation in recent years to overcome the second discontinuity. By this, we mean tasks that are situated by typical everyday challenges of mathematics teaching and in which PSTs must use their mathematical knowledge and skills in a professionally relevant way. In this paper, we analyze answers that PSTs have created to an interface task on symmetry. The PSTs were asked to clarify a student’s question from a mathematical perspective and then give a suitable elementarized answer. We situate these two steps theoretically and reconstruct the mathematical reasoning in PSTs' answers. Through qualitative content analysis, we examined how PSTs justify figures' symmetries from a university mathematics perspective and when responding to the fictitious student. The scenario of a student questioning the existence of 100° rotationally symmetrical figures elicited rich and varied responses, proving suitable for an interface task. We compared PSTs' reasoning related to mathematical clarification with the reasoning related to elementarization. In many cases, this revealed a productive use of course content. An interesting result is that there is no uniform picture as to whether the arguments are more detailed in the mathematical clarification or in the elementarization.

The Laplace transform in Dunkl theory - Brennecken, Dominik; Rösler, Margit (Women in Analysis and PDE)

The Condemnation of Hate and the Violence of the Status Quo - Althoff, Sebastian (Cultural Politics)
This article interrogates the tension between the way that the condemnation of hate performatively establishes and reinforces discursive and affective boundaries for public debates and the embrace of hate by anti-racist, abolitionist, feminist, and queer activists, that is, their claim that hatred is a valid response to the existential violence inflicted by borders or the police. The cases of activists embracing hate indicate that the boundaries set by the condemnation of hate are too limited to appropriately account for the violence of the status quo. The condemnation of hate, rather, appears to veil this violence, that is, as a way to curb the means to critique and overcome the status quo. The article offers a critical engagement with studies on hate that pathologize the hateful subject, juxtaposing these studies with cases of activists affirming their hatred for politicians, straight people, or San Francisco tech workers. It thereby broadens understandings of hate by proposing that hate as a response to harm can be part of anti-racist, abolitionist, feminist, and queer struggles and provide valuable epistemic effects grounded in theory rather than conspiracies. The article consequently challenges the condemnation of hate by contesting that hate is necessarily illegitimate.

Produktives Fördern im inklusiven Mathematikunterricht - Häsel-Weide, Uta; Nührenbörger, M. (Inklusives Lehren und Lernen von Mathematik: Konzepte und Beispiele mit Fokus auf Grund- und Förderschule)